In Vitro Evaluation of Bacillus subtilis and Pseudomonas fluorescens Against Klebsiella variicola in Kepok Banana - Graciella Luise Laoth; Gusti Ngurah Alit Susanta Wirya; I Gede Rai Maya Temaja (Research Horizon, 2026)
Bacterial wilt represents a major constraint in the cultivation of Kepok banana (Musa paradisiaca L.) in East Nusa Tenggara, and recent identification of Klebsiella variicola as the causal agent indicates a potential emerging threat to production sustainability. This study aimed to evaluate the antagonistic potential of Bacillus subtilis and Pseudomonas fluorescens against K. variicola under in vitro conditions. The experiment was arranged in a Completely Randomized Design with five treatments, including control groups, single antagonistic bacteria, and their combination, using a dual culture assay with the paper disc method. The results demonstrated that Bacillus subtilis exhibited the highest inhibitory activity, followed by the combination treatment and Pseudomonas fluorescens, while no inhibition was observed in the negative control. The superior performance of Bacillus subtilis is associated with its ability to produce antibacterial metabolites, particularly lipopeptides that disrupt pathogen cell structures. In contrast, Pseudomonas fluorescens inhibited pathogen growth through siderophores and toxic compounds, although with lower effectiveness. The combination treatment did not produce a synergistic effect, likely due to microbial competition. These findings suggest that Bacillus subtilis holds strong potential as an environmentally friendly biological control agent. Further in vivo studies are required to validate its effectiveness under field conditions.